IMPLEMENTATION OF ACCELERATED CULTURAL HERITAGE DATA COLLECTION BASED ON GOVERNMENT REGULATION NO. 1 OF 2022 IN SERANG CITY - Dewi Lestari Purba; H.E Rakhmat Jazuli; Ahmad Rayhan (PT. Jurnal Center Indonesia Publisher, 2026)
Accelerating cultural heritage data collection in Serang City is a strategic step in efforts to preserve cultural heritage in accordance with the mandate of Law Number 11 of 2010 concerning Cultural Heritage and Government Regulation Number 1 of 2022 concerning National Registers and Cultural Heritage Preservation, which aims to provide accurate cultural heritage data as a basis for legal protection and preservation policies. Implementation is not optimal, as there are still suspected reserve objects (ODCB) that have not been officially determined. This research identifies the problem, namely, How is the Implementation of Accelerated Cultural Heritage Data Collection in Supporting Cultural Heritage Preservation in Serang City and what are the obstacles. This research uses authority theory and cultural heritage conservation theory as the basis for analysis. The research method used is empirical juridical with a qualitative descriptive approach through literature studies and interviews with related parties. The research results show that the acceleration of data collection has been carried out through activities to identify, verify, and record cultural heritage objects in the Dapobud system. This step, according to regulations, produces more accurate data, so that it can be immediately protected and preserved. However, implementation has not been optimal due to obstacles in the form of limited facilities and infrastructure, budget, human resources, constraints on the Dapobud system, lack of local government support, and community participation. The conclusion is that the implementation of accelerated data collection on cultural heritage in Serang City has made a positive contribution to conservation efforts, even though it still faces obstacles. Recommendations are addressed to the Serang City Government to strengthen budget support, increase human resource capacity, prepare supporting facilities, and encourage collaboration and community participation so that preservation can be sustainable.